Variability of Prehospital Pain Management Protocols: A Review of Prehospital Care Protocols in the United States - Li T; Koloden D; Berkowitz J; Luo D; Luan H; Gilley C; Kurgansky G; Howell DM; Barbara P (Open Access Emergency Medicine, 2024)
Timmy Li, Daniel Koloden, Jonathan Berkowitz, Dee Luo, Howard Luan, Charles Gilley, Gregory Kurgansky, Devin M Howell, Paul Barbara Department of Emergency Medicine, Northwell, New Hyde Park, NY, USACorrespondence: Timmy Li, Department of Emergency Medicine, Northwell, 2000 Marcus Ave, Suite 300, New Hyde Park, NY, 11042-1069, USA, Tel +1 516 240-3933, Email TLi2@northwell.eduPurpose: We describe emergency medical services (EMS) protocols for pain management in the United States to elucidate systemic variability in protocols. We describe types of pain medications included in protocols, routes of administration, indications for use, standing orders for dosing, and use in pediatric patients.Methods: We performed a review of all publicly accessible EMS protocols from the website http://www.emsprotocols.org, supplemented with internet searches. Data were abstracted into a data collection form from June 2021 to January 2022. We developed categories of responses to summarize the data, using frequencies and proportions to describe outcome measures.Results: We reviewed 104 EMS protocols, spanning 43 states. The most common pain management medications include fentanyl (94.2%), morphine (70.2%), ketamine (61.5%), ketorolac (40.4%), oral acetaminophen (36.5%), oral ibuprofen (22.1%), and nitrous oxide (19.2%). The most common route of administration across all protocols and medications is intravenous. Severe pain, without a specified level, is the most common indication for fentanyl (65.3%), morphine (61.6%), ketorolac (50.0%), and nitrous oxide (40.0%). Musculoskeletal injuries and burns are the most common indications for morphine, 15.1% and 19.2% of protocols, respectively. The majority of protocols dictate the weight-based dosing of fentanyl (74.5%), morphine (64.4%), ketamine (87.3%), oral acetaminophen (56.8%), and oral ibuprofen (59.1%). However, 97.6% and 100.0% of protocols dictate a fixed dose of ketorolac and nitrous oxide, respectively. Fentanyl, morphine, oral acetaminophen, and oral ibuprofen can be administered to pediatric patients based on standing orders among > 90.0% of protocols. However, only 46.2% and 75.0% of protocols allow the use of ketorolac and nitrous oxide in pediatric patients, respectively.Conclusion: We found variability in EMS pain management protocols including the types of allowed medications, routes of administration, dosing, and indications for use. Further studies may assess whether standardized protocols across EMS systems could improve patient safety and quality of care.Keywords: pain management, pediatrics, emergency medical services, protocols, variability